PHONETIC EXPRESSION AS A MECHANISM OF MEANING FORMATION IN THE LYRICS OF RUSSIAN ROMANTICISM OF THE 19th CENTURY - Ataboeva Laylo Tolipovna (Western European Studies, 2026)
The article is devoted to the study of phonetic means of expression in poetic texts and their role in the formation of artistic meaning. The paper examines the problem of a comprehensive analysis of expression as a multi-level category that integrates emotionality, evaluation, and aesthetic impact. Particular attention is paid to the phonetic level of language, which in poetic speech functions not only as a means of sound organization of the text but also as an important component of meaning formation. The theoretical basis of the study is formed by the works of Russian linguists and literary scholars devoted to the issues of artistic expressiveness, the poetic function of language, and the interaction between form and content. The research analyzes sound instrumentation, alliteration, assonance, rhythmic and intonational organization of poetic text as means of realizing the expressive potential of language.
Keywords: Phonetic expression; poetic text; sound instrumentation